The INSTANT Model: Developing Digital Literacy to Enhance Professional Competence of Islamic Religious Education Teachers - Miftahul Fikri; Aan Hasanah; Bambang Samsul Arifin; Andewi Suhartini; Roman Tsarev (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
Teachers hold moral and professional responsibility in guiding student development. Professional competence includes content mastery, pedagogy, technology, and professional growth. Religious teachers must integrate digital literacy to enhance professional performance. Digital literacy helps teachers access, process, and share information effectively. Teachers with strong digital skills improve teaching relevance and student engagement. This study aims to develop a conceptual model for digital literacy enhancement. It focuses on Islamic Religious Education teachers in Indonesian secondary schools. This research used a Research and Development (R&D) approach. The Four-D method was applied: Define, Design, Develop, Disseminate. Data were collected through surveys, interviews, observations, tests, and documentation. Respondents were Islamic Education teachers in West Java. The result is the INSTANT Model for digital literacy training. The model includes: Introduction, Need-based, Scaffolding, Training, Application, Nurturing, and Test. It incorporates constructivism, connectivism, cognitive, social, and experiential learning theories. Experts and users validated the model’s practicality and effectiveness. The model improved teachers' skills with an average N-Gain of 74.4% (high category). Stakeholders positively received the model in various dissemination formats. The INSTANT Model offers a practical framework for teacher digital competence development. Keywords: Digital Literacy; INSTANT Model; Professional Competence.